OHVIRA-syndrome in a newborn - J. Kueppers; L. Wehrli; S. Zundel; S. Shavit; N. Stahr; P.O. Szavay (Elsevier, 2021)
OHVIRA-Syndrome (Obstructed hemivagina with ipsilateral renal anomaly) is a rare congenital malformation. Diagnosis of this malformation is usually made during adolescence. Delayed diagnosis may result in serious complications with potential future obstetric problems. We report on a newborn girl presenting with an interlabial mass formation, a vaginal introitus on the right lateral aspect and an orthotopic urethral meatus on primary inspection. Ultrasound examination revealed left sided renal agenesis and a hydrocolpos posterior to the bladder. OHVIRA-Syndrome was assumed and a surgical incision of the obstructed left hemivagina for drainage of the hydrocolpos was performed. Further examination confirmed anatomical conditions corresponding to OHVIRA-Syndrome. Aside from routine clinical follow-up and regular ultrasound examination, further interventions were postponed until puberty. In this case report we aim to share our experience of a newborn girl with OHVIRA-Syndrome. We discuss appropriate medical decision-making regarding surgical management of patients with this malformation during each stage of development with a corresponding literature review.